Barbs (submerged groynes) for river bend bank protection: Application of a three-dimensional numerical model - Minor, Barbara (University of Ottawa (Canada), 2006)
A three-dimensional numerical model was used to examine the turbulent flow field and associated sediment transport due to a series of barbs in a channel bend. It was observed that the results simulated by the model showed good agreement with measured data and adequately simulated the important features of sediment transport. Statistical analysis of the predicted and measured sediment transport results found an average regression coefficient of determination of 0.8 for the 90 and 135° channels. It was found that the predicted velocity data followed expected trends. The following objectives were achieved: validation of the application of a three-dimensional numerical model to bend sections of a channel containing barbs; simulation of the effects of different arrangements of barb groups; and analysis of the data to determine the relation of the flow field to associated scour and deposition in a complex fluvial environment. These novel data are useful for improved analyses of the bank protection capabilities of these structures and for the development and improvement of design guidelines.
Keywords: Engineering, Civil.